Miguel Pachas Almeida, ¡Yo que tan solo he nacido! (A biography of César Vallejo). Lima: Editorial Gutemberg, 2018, 647 pp. - Carhuaricra Anco, Miguel Ángel (2019)
Writing a few lines about the life and work of César Vallejo is always a project that gets any biographer or literary critic frothy.